A Prospective Study of Weight and Metabolic Syndrome in Young Hispanic Children - Patiño-Fernández, Anna Maria (2008)
OBJECTIVE: Examine weight in young Hispanic children over a two-year period; investigate the relationships among overweight, physical activity, caloric intake, and family history in the development of the metabolic syndrome (MS). METHODS: Forty-seven children (ages 5–8) from diverse Hispanic backgrounds recruited from elementary schools were evaluated. Laboratory analyses, anthropometric data, and measures of physical activity and caloric intake were included. RESULTS: The majority of the children were overweight at baseline (66%) and at follow-up (72%). Children who were overweight at baseline were more likely to exhibit MS at follow-up than were those who were not overweight at baseline. CONCLUSIONS: Overweight appears to be an independent predictor of MS among Hispanic children.